Perancangan Alat Penghitung Benih Ikan Berbasis Sensor Optik - Purbowaskito, Widagdo; Handoyo, R. (Rekayasa Mesin, 2017)
Freshwater fish is one of important commodities for the people of Indonesia. High level of freshwater fish consumption in Indonesia leads to an enormous amount of freshwater fish embankment business. These freshwater fish embankment business are supported by fries cultivation business. One of the activities on the fries cultivation business is trading activity where the traded fries counting process is important. One of the problems on the counting process is that the counting process is done manually which is tend to be done inaccurately and time consuming. A proposed solution to alleviate this problem is the development of fries counter device by using optical sensor technology. The counter device consists of mechanical and electronics systems. The device is designed as a plastic box with three distribution pipes where on each pipe there is a transparent part installed with the optical sensor. Based on the testing results the optical sensor can be utilized as the counter sensor with accuracy result 91.4%.